Chronic thromboembolic pulmonary hypertension: evaluation of V/Q SPECT/CT and V/Q Quotient SPECT findings with postoperative results of pulmonary endarterectomy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Objectives We aimed to perform a comparison between V/Q single-photon emission computed tomography/computed tomography (SPECT/CT) and V/Q Quotient single-photon emission computerized tomography (SPECT) in the detection of chronic thromboembolic pulmonary hypertension (CTEPH) and in depicting the extent of the disease on per-segment basis in patients with CTEPH. Methods Between January 2015 and November 2019, a total of 412 patients with pulmonary hypertension secondary to CTEPH at the preoperative assessment underwent pulmonary endarterectomy (PEA), of whom 92 consecutive patients with their V/Q SPECT/CT scans have been performed in our institution prior to PEA were included in this study. Histopathological findings and post-PEA fully resected surgical specimens were used as the reference standard. Results On a per-patient basis analysis, V/Q SPECT/CT and V/Q Quotient SPECT both revealed CTEPH in the same 85 of the 92 patients (kappa = 1) with a detection rate of 92.4%. In six of these patients, chronic thromboembolic disease could not be reported on both of these two methods due to extensive 'matched' V/Q defects. On a per-segment basis analysis, V/Q SPECT/CT and V/Q Quotient SPECT showed a sensitivity of 75.8 and 73.1%, respectively. Correlation analysis results showed a significant correlation (kappa = 0.933) between these two methods on a per-segment basis analysis. Conclusion In the light of histopathological findings and post-PEA surgical specimen examinations, the results of the present study indicated that both V/Q SPECT/CT and V/Q Quotient SPECT showed relatively high efficacy for the detection of CTEPH on per-patient and per-segment bases with an excellent agreement.
Keywords: endarterectomy; hypertension; pulmonary; pulmonary embolism; single-photon emission computed tomography; computed tomography; Ventilation– perfusion scan